Perbandingan Pengelolaan Sistem Irigasi Tetes Pada Tanaman Melon dan Cabai - Tri Handayani (Manajemen Agribisnis: Jurnal Agribisnis, 2023)
The use of drip irrigation is currently increasingly recognized by the community, especially in areas where the level of irrigation management is difficult. This is a solution for handling irrigation so that the commodity crops cultivated are still good but the irrigation costs can be reduced. Drip irrigation systems have been widely applied to vegetable and fruit crops. This study aims to compare effectively and qualitatively the use of drip irrigation systems on 2 types of plants, namely melon plants and chili plants. The method used is descriptive qualitative, where the variables compared are the water requirements of each plant phase, the uniformity of plant growth, and the need for operational costs. The results of the comparison of melon plants with chili plants using a drip irrigation system on cultivation parameters produced good results, where all the observed variables showed an increase in growth rate where the average was in the fertilization phase. Meanwhile, in the calculation of operational costs, it suffers a loss if it is only planted once